Sekularisasi Kesadaran Dan Penafsiran Ulang Doktrin-Doktrin Agama - Hanif, Abdulloh (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2017)
The Modern Age gave rise to secular ideology. Religionists got worry about religion that is getting out of the community of life. Research proves that secularization has revolutionized the religion of society with the traditions they carry. Turas (tradition) in this context is dogma, that is, something that has the truth and is based on religious texts. It can be either the text itself or the thought. In order to appreciate Turas as a dogma in the modern world, it must undergo a process of secularization. In this case, turats should be viewed live with the community and historic. Turas is not a transcendent element apart from the life of society. Hassan Hanafi and Khaled Abou el-Fadl received secularization and led him to revise the meaning of tura by using three approaches in reading turats, revolutions, transcendence, and hermeneutics. Secularization is not the abandonment of religious dogma but it reconstructs the appropriate meaning.